2018
DOI: 10.1186/s13058-018-1072-1
|View full text |Cite
|
Sign up to set email alerts
|

HER4 expression in estrogen receptor-positive breast cancer is associated with decreased sensitivity to tamoxifen treatment and reduced overall survival of postmenopausal women

Abstract: BackgroundThe sensitivity of estrogen receptor-positive breast cancers to tamoxifen treatment varies considerably, and the molecular mechanisms affecting the response rates are manifold. The human epidermal growth factor receptor-related receptor HER2 is known to trigger intracellular signaling cascades that modulate the activity of coregulators of the estrogen receptor which, in turn, reduces the cell sensitivity to tamoxifen treatment. However, the impact of HER2-related receptor tyrosine kinases HER1, HER3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…Years ago, HER4 (i.e., 4ICD) has already been shown to co-activate estrogen receptor related transcription and thereby to promote tumor cell growth and proliferation [15, 29]. Based on this finding and other evidences we recently demonstrated an improved outcome of ER positive and tamoxifen treated postmenopausal breast cancer patients in the absence of HER4 expression [30]. In contrast, we found no impact of HER4 in patients treated with aromatase inhibitors which indicated some kind of 4ICD/ER/tamoxifen interaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Years ago, HER4 (i.e., 4ICD) has already been shown to co-activate estrogen receptor related transcription and thereby to promote tumor cell growth and proliferation [15, 29]. Based on this finding and other evidences we recently demonstrated an improved outcome of ER positive and tamoxifen treated postmenopausal breast cancer patients in the absence of HER4 expression [30]. In contrast, we found no impact of HER4 in patients treated with aromatase inhibitors which indicated some kind of 4ICD/ER/tamoxifen interaction.…”
mentioning
confidence: 99%
“…Overall, we revealed strong evidence that HER4 (or more specifically 4ICD) impedes the tamoxifen-estrogen receptor interaction and thereby attenuates the tamoxifen treatment efficiency. Accordingly, we provided a model of action of the molecular troika consisting of 4ICD/ER/tamoxifen that explains an improved response to tamoxifen treatment in the absence and an impaired response in the presence of HER4 [30].…”
mentioning
confidence: 99%
“…An advantageous impact of HER4 expression in breast cancer has been mechanistically attributed to ligand-dependent (i.e., HRG) receptor activation and the subsequent triggering of differentiation pathways that in turn antagonize oncogenic cellular features generated by other coexpressed HER receptor family members, above all HER2. It is assumed that via HER4-mediated signaling an interaction with the ER pathway occurs, leading to an improved outcome of ER-positive and tamoxifen-treated postmenopausal breast cancer patients in the absence of HER4 expression [41]. HER4 may also play a key role in the survival of HER2-positive cancer cells after they de-velop resistance to the anti-HER2 inhibitors lapatinib and trastuzumab [42].…”
Section: Targeting Her4mentioning
confidence: 99%
“…Genetic alterations in ERBB4, namely, rs13423759, not only enhance breast cancer risk but are also associated with the increased metastasis in patients with breast cancer (Mansouri Bidkani et al, 2018). The interaction between HER4 and ER hinders the binding of tamoxifen to the ER, thereby inducing tamoxifen resistance (Wege et al, 2018). Moreover, the same author demonstrated that the overexpression of HER4 reduces the overall survival of postmenopausal women.…”
Section: Proposed Ptgs and The Mechanism Of Berberine In Overcoming Bmentioning
confidence: 99%